The Mediating Role of Customer Satisfaction Between Service Quality and Customer Loyalty According to An Islamic Perspective - Imari, Iqbal '; Suminto, Ahmad; Gololo, Ibrahim Aliyu (IKONOMIKA, 2021)
This study aims at determining whether customer satisfaction mediates the relationship between service quality and customer loyalty in La-Tansa Transport Gontor, then analyze it with the Islamic principles. This study is quantitative with primary data which is in the form of questionnaires filled by 109 customers. Service quality, customer satisfaction, and customer loyalty were measured in 5-scale likert. Regression analysis was used to analyse the mediating effect. The result shows that customer satisfaction is a mediating variable between service quality and customer loyalty. These results indicate that customers of La-Tansa Transport get sufficient service quality, feel satisfied towards the service, and have had the loyalty to the business. It could be explained because La-Tansa Transport follows the Islamic values in providing service and engaging with customers